Asas-Asas Perjanjian dalam Hukum Perjanjian Islam - Ubaidullah Muayyad ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2015)
This paper explains that the agreement is basically contained the principle of freedom of contract should not be restricted by anyone even including legislation. But subsequent developments, the Indonesian legal practice, the agreement is based on this principle in the form of their failure to intervene parliament through legislation on freedom of contract. While in Islamic law, the principle of freedom of contract is not absolute, but limited. In principle, not much different from the limitations under positive law. In the Islamic Shari'a law are the principles of the agreement are divided into several basic principles, namely the principle of tawhid, the permissibility, freedom of contract, justice, equality, honesty, trust, benefit and welfare, konsensualisme, binding promise, achievement of balance, legal certainty, and personality.